Low level RF development for ESS high beta cavity test. Issue 1 (1st May 2022) - Dumbell, K; Lewis, J; Wheelhouse, A; Pattalwar, S; Moss, A; Corlett, P; Goudket, P; Hitchen, S; Jenkins, C; Ellis, M; Pendleton, M; Smith, P; et al.
Abstract: Testing of superconducting cavities requires the use of a Self-Excited Loop or Phase Locked Loop in order to track a cavity's resonant frequency under the disturbances of micro-phonics. Many laboratories have successfully developed their own Low Level RF solutions and have implemented these using Field Programmable Gate Array at the heart of the digital system. This approach has also been adopted at Daresbury Laboratory. However, the dedicated system was identified as a single point of failure in the complex operational testing infrastructure and an alternative, back-up, system was sought. Rather than duplicate the existing system another approach has been adopted making use of Commercial Off The Shelf hardware with minimal requirement for interconnect to the existing high power system. The solution is based around the NI (National Instruments Corporation) FlexRIO transceiver adapter NI-5782 connected to the NI-7962R FPGA module inside a PXI chassis. This system is capable of working directly at an Intermediate frequency of 37.5 MHz and only requires a simple up-converter / down-converter stage. Testing the high Q (typically 2 × 10 10 ) cavities up to accelerating gradients of 22.5 MV/m has been successful.